2008
DOI: 10.1152/ajprenal.00063.2008
|View full text |Cite
|
Sign up to set email alerts
|

Lower urogenital tract anatomical and functional phenotype in lysyl oxidase like-1 knockout mice resembles female pelvic floor dysfunction in humans

Abstract: Female pelvic floor dysfunction (FPFD) is a complex group of conditions that include urinary incontinence and pelvic organ prolapse (POP). In humans, elastin homeostasis has been implicated in the pathophysiology of FPFD. Lysyl oxidase-like 1 knockout (LOXL1-KO) mice demonstrate abnormal elastic fiber homeostasis and develop FPFD after parturition. We compared the lower urogenital tract (LUT) anatomy and function in LOXL1-KO mice with and without POP. LUT anatomy was assessed in LOXL1-KO mice over 28 wk. Pelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
57
1
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 62 publications
(66 citation statements)
references
References 29 publications
5
57
1
3
Order By: Relevance
“…NHP are often considered ideal; however, they are not strictly bipedal, they are small, and their Post hoc Jonkheere-Terpstra: *P < 0.05; **P, 0.01, ***P < 0.0001 compared with nulliparous cost is extremely limiting [23]. The pelvic floor anatomy of rodents is more horizontal than that in humans, and offspring have a much smaller fetal head-to-birth-canal ratio [24]. Their small size makes it almost impossible for clinical examination or surgery to compare with humans.…”
Section: Discussionmentioning
confidence: 99%
“…NHP are often considered ideal; however, they are not strictly bipedal, they are small, and their Post hoc Jonkheere-Terpstra: *P < 0.05; **P, 0.01, ***P < 0.0001 compared with nulliparous cost is extremely limiting [23]. The pelvic floor anatomy of rodents is more horizontal than that in humans, and offspring have a much smaller fetal head-to-birth-canal ratio [24]. Their small size makes it almost impossible for clinical examination or surgery to compare with humans.…”
Section: Discussionmentioning
confidence: 99%
“…22,25 Additionally, this data helps further explain our previous study of lower urinary tract function in Loxl1 KO mice in which we showed that parity significantly contributed to lower leak point pressures. 12 Overall, our data suggest that Loxl1 deficiency results in aberrant antepartum and postpartum gene expression responses to pregnancy and parturition that may be exacerbated by vaginal delivery.…”
Section: Discussionmentioning
confidence: 63%
“…14,28 In addition, POP in Loxl1 KO mice simulates the phenotype of POP in women, with vaginal delivery as a major risk factor, often affecting voiding function, and progressing with age. 1,11,12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ewies et al (2003) and Karam et al (2007) demonstrated ) knockout mice with evidence of disrupted elastin fibers (Drewes et al, 2007). Lysyl oxidase-like1 (LOXL1) is a protein involved in the elastin fiber synthesis and assembly and LOXL1 knockout mice exhibit significant elastin fiber defects and POP in the postpartum period (Lee et al, 2008). POP has also been associated with cutis laxa, a genetic disorder with unclear etiology but associated with markedly decreased elastin (Paladini et al, 2007).…”
Section: Commentmentioning
confidence: 99%